Achievements and some unsolved problems of the finite element method - Zienkiewicz, O. C. (International journal for numerical methods in engineering, 2000)
After outlining the early history of the finite element method the paper concentrates on to (1) some important achievements of the last decade and (2) presents an outline of some problems still requiring treatement. In the first part, the developments of the patch test for assessment of elements, new developments of adaptive refinement and the principles of the general CBS algorithm for fluid dynamics are presented. Copyright © 2000 John Wiley & Sons, Ltd.